The old man and Slovenia: Hemingway studies in the slovenian cultural context - Igor Maver (Acta Neophilologica, 1990)
The name of Ernest Hemingway was first mentioned in Slovenian literary criticism by the writer and critic Tone Seliškar in 1933. Soon afterwards, Griša Koritnik, the foremost translator of English and American literatures in the period between the two wars, in his article »The Great War in the English Novel« described the protagonist of the novel A Farewell to Arms (1929) somewhat enigmatically as »the symbol of the old generation«. In a short survey of contemporary American literature, which Anton Debeljak in 1939 freely adapted from the article previously published by J. Wood Krutch in The Times,  Hemingway was grouped together with the Nobel Prize winner Pearl S. Buck and novelist Erskine Caldwell, which is to say with the giants of the then mainstream American fiction. However, it is curious that a Slovenian reader should already from this article have learned how Hemingway, the author of »powerful stories«, had recently become monotonous, which was before he even had a fair chance to get acquainted with any of his works translated into Slovenian.